Grey matter abnormalities in methcathinone abusers with a Parkinsonian syndrome. Issue 11 (18th August 2016) - Juurmaa, Julius; Menke, Ricarda A. L.; Vila, Pierre; Müürsepp, Andreas; Tomberg, Tiiu; Ilves, Pilvi; Nigul, Mait; Johansen‐Berg, Heidi; Donaghy, Michael; Stagg, Charlotte J.; Stepens, Ainārs; Taba, Pille
Abstract: Background: A permanent Parkinsonian syndrome occurs in intravenous abusers of the designer psychostimulant methcathinone (ephedrone). It is attributed to deposition of contaminant manganese, as reflected by characteristic globus pallidus hyperintensity on T1‐weighted MRI. Methods: We have investigated brain structure and function in methcathinone abusers ( n  = 12) compared to matched control subjects ( n  = 12) using T1‐weighted structural and resting‐state functional MRI. Results: Segmentation analysis revealed significant ( p  < .05) subcortical grey matter atrophy in methcathinone abusers within putamen and thalamus bilaterally, and the left caudate nucleus. The volume of the caudate nuclei correlated inversely with duration of methcathinone abuse. Voxel‐based morphometry showed patients to have significant grey matter loss ( p  < .05) bilaterally in the putamina and caudate nucleus. Surface‐based analysis demonstrated nine clusters of cerebral cortical thinning in methcathinone abusers, with relative sparing of prefrontal, parieto‐occipital, and temporal regions. Resting‐state functional MRI analysis showed increased functional connectivity within the motor network of patients ( p  < .05), particularly within the right primary motor cortex. Conclusion: Taken together, these results suggest that the manganese exposure associated with prolonged methcathinone abuse results in widespread structural and functional changes affecting both subcortical and cortical grey matter and their connections. Underlying the distinctive movement disorder caused by methcathinone abuse, there is a more widespread pattern of brain involvement than is evident from the hyperintensity restricted to the basal ganglia as shown by T1‐weighted structural MRI. Abstract : Recently, a distinctive clinical syndrome has been described in ephedrone abusers, consisting of an irreversible extrapyramidal disorder, made remarkable by highly specific clinical symptoms of hypokinesia, dysarthria, dystonia, and postural instability. Here, we have used advanced MR techniques including voxel‐based morphometry and FreeSurfer to demonstrate abnormalities in subcortical structures, in particular the caudate nucleus, where abnormally low volumes in patients are related to the length of ephedrone abuse. In addition, in line with the remarkable clinical syndrome, we demonstrate for the first time widespread thinning of the cortex, and show changes in functional connectivity within patients compared with controls.